Temperature-dependent water retention and bleeding of fresh cement-based materials with VEAs. (July 2022) - Gu, Linan; Liu, Tiejun; Wu, Kai; Yang, Zhenghong; Wen, Zhaoyin; Zhang, Zhenlei; Li, Haoxin
Abstract: It is still uncertain whether temperature exerts some influence on the water retention (WR) and bleeding of cement-based materials with viscosity-enhancing admixtures (VEAs). Thus, WR and bleeding of cement-based materials with selected VEAs, such as sodium polyacrylate (PANA), hydroxyethoxy methoxy cellulose (HEMC) and hydroxypropoxy methoxy cellulose (HPMC), were evaluated at 20, 30, 40, 50, and 60 °C, and experiments on the apparent viscosity, total organic carbon (TOC) content, hydrodynamic radius and thermogravimetry were carried out to explore the responsible mechanisms. The results show that VEAs enhance WR and reduce bleeding at room temperature to varying degrees. However, this improvement at higher temperature does not occur as at room temperature (20 °C). The decreased improvements in WR and bleeding at higher temperature are associated with the lowered apparent viscosity, TOC content, hydrodynamic radius and the increased cement hydration. Below 40 °C, the apparent viscosity, adsorption and hydrodynamic radius dominate the bleeding behaviour of mortars with HPMC and HEMC. However, accelerated cement hydration is mainly responsible for the behaviour when the temperature exceeds 40 °C.